Histopathology of cultured sea bass (Lates calcarifer) (Centropomidae) infected with Cruoricola lates (Trematoda: Sanguinicolidae) from Pulau Ketam, Malaysia - Herbert, B.W.; Shaharom, F.M.; Anderson, I.G. (Elsevier, 1995)
Cruoricola lates are found throughout sea bass (Lates calcarifer), most commonly in the mesenteric blood vessels, kidney, pericardial vessels, and eye. Eggs of C. lates were predominantly found in the gills, ventricle, hepatopancreas, and kidneys, but only develop to miracidia regularly in the gills and heart. Single miracidia escaping appear to cause little damage, but groups induce an inflammatory response and haemorrhage. Endocardial macrphages encapsulate eggs trapped between trabeculae in the heart. The reaction to eggs in the kidneys, hepatopancreas and spleen consists of fibrocytic encapsulation. Infection at the levels observed in this study were insufficient to cause lethal pathological changes, but could result in reduced food conversion ratios or impaired immunological capacity.